Does the old-age pension scheme improve household welfare? Evidence from India. (October 2020) - Unnikrishnan, Vidhya; Imai, Katsushi S.
Highlights: This paper finds that participation in IGNOAPS has a strong positive effect on various household welfare dimensions. Welfare dimensions studied here includes monthly consumption expenditure, food, non-food expenditures, and household assets. The program has a negative effect on household labour supply. The sub-sample estimations show that these effects are observed only when recipients are women. Poverty-reducing effect deteriorated in 2011–12 after the government made several changes to programme specifications. Abstract: As India's population has been ageing due to declines in fertility and mortality rates, more policy emphasis has been placed on reducing poverty among the elderly. The present study aims to examine the effect of Indira Gandhi National Old Age Pension Scheme (IGNOAPS) on household welfare indicators, such as consumption expenditure, income, assets, and poverty. Using the household longitudinal data based on the India Human Development Survey in 2004–5 and 2011–12, we have applied the Propensity Score Matching to build a counterfactual group and have used the propensity-score weighted fixed effects model to eliminate time-invariant unobservable household characteristics. The results show that the IGNOAPS participation increased consumption expenditure, food and non-food expenditure and assets, while reducing the household labour supply. The sub-sample estimations show that these effects are observed only when recipients are women. However, the results of Difference-in-Difference model imply that the poverty-reducing effect deteriorated in 2011–12 after the government made several changes to programme specifications in 2007. This was likely because some households which accessed IGNOAPS after 2007 reduced the labour supply significantly while keeping the level of consumption.